2011
DOI: 10.1051/limn/2011020
|View full text |Cite
|
Sign up to set email alerts
|

Distribution patterns of fish communities with respect to environmental gradients in Korean streams

Abstract: -Stream development can generate environmental changes that impact fish communities. In temperate streams, the distribution of fish species is associated with environmental gradients. To analyze the relevant factors, large-scale exploration is required. Thus, to evaluate the distribution patterns of fish in Korea, sampling was conducted on a national scale at 720 sites over a 6-week period in 2009. A total of 124 fish species in 27 families were identified; Zacco platypus and Zacco koreanus of the Cyprinidae w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 36 publications
(36 reference statements)
3
13
0
Order By: Relevance
“…Our results fitted very well with previous research that showed altitude considerably affects fish distribution in aquatic ecosystems (Amarasinghe & Welcomme 2002;Yoon et al 2011;Barradas et al 2012;Stojkovic et al 2013). However, altitude is a complex variable: it can cause direct and indirect effects on fish distribution.…”
Section: Potential Determinants Of Lake Fish Diversity and Assemblagessupporting
confidence: 91%
“…Our results fitted very well with previous research that showed altitude considerably affects fish distribution in aquatic ecosystems (Amarasinghe & Welcomme 2002;Yoon et al 2011;Barradas et al 2012;Stojkovic et al 2013). However, altitude is a complex variable: it can cause direct and indirect effects on fish distribution.…”
Section: Potential Determinants Of Lake Fish Diversity and Assemblagessupporting
confidence: 91%
“…All the fish captured were identified to species level in the field (Kim and Park, 2002), counted and released. The individuals whose length were less than 20 mm were preserved in 10% formalin and identified in the laboratories (Lee et al, 2011a;Yoon et al, 2011).…”
Section: Community Datamentioning
confidence: 99%
“…Generally, altitude could generate direct barrier effects on distribution and life history traits of organisms, e.g. limit the colonization and speciation of fish (Yoon et al, 2011;Barradas et al, 2012;Stojkovic et al, 2013). As a complex variable, altitude can also bring indirect impacts on fish assemblages due to collinearity with climatic factors (Brucet et al, 2013).…”
Section: Prediction and Determinants Of Fish Species Assemblages In Cmentioning
confidence: 99%